John Farnell and James Elles, In Search of a Common Fisheries Policy, Aldershot: Gower, 1984, 213 s., 28.50 $; Michael Leigh, European Integration and the Common Fisheries Policy, London: Croom Helm, 1983, 228 s. - Laursen, Finn (Politica, 1984)
-